Numerical modelling in research on geothermal systems - Dendys, Marta; Tomaszewska, Barbara; Pająk, Leszek (Bulletin of Geography. Physical Geography Series, 2015)
Nowadays, numerical modelling is a common tool for support research of geothermal systems. This is possible because of development of computer sciences and access to software dedicated to numerical modelling of hydrogeological processes. With computer applications researches can do scheme of hydrogeological conditions and simulate work of geothermal systems and thermal water intakes. Researches create numerical models of geothermal systems in regional and local scale, for simulating work of specific thermal water formation and intakes and their particular elements - well active zone for example. In parallel with the economic development of the use of thermal water in Poland there are a lot of research projects where numerical modelling occurs as a primary or supporting tool. This paper provides an overview of research issues where the solution of the problem was found with using computer application and numerical simulators.